2015
DOI: 10.5114/jcb.2015.54947
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided high-dose rate brachytherapy: preliminary outcomes and toxicity of a joint interventional radiology and radiation oncology technique for achieving local control in challenging cases

Abstract: PurposeTo determine the ability of image-guided high-dose-rate brachytherapy (IG-HDR) to provide local control (LC) of lesions in non-traditional locations for patients with heavily pre-treated malignancies.Material and methodsThis retrospective series included 18 patients treated between 2012 and 2014 with IG-HDR, either in combination with external beam radiotherapy (EBRT; n = 9) or as monotherapy (n = 9). Lesions were located in the pelvis (n = 5), extremity (n = 2), abdomen/retroperitoneum (n = 9), and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Similarly, to other studies, no complications occurred during application and no early toxicity was observed [22, 23, 24]. Moreover, positive effects were achieved in case of both treatment efficiency and quality of life.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similarly, to other studies, no complications occurred during application and no early toxicity was observed [22, 23, 24]. Moreover, positive effects were achieved in case of both treatment efficiency and quality of life.…”
Section: Discussionsupporting
confidence: 80%
“…In a study by Kishan et al . [24] data were retrospectively analyzed from 18 patients with cancer, located in various areas including 2 in the head and neck area, who had undergone HDR brachytherapy performed under guidance of different imaging methods. Various dose fractioning schemes were used: 6 Gy in 6 fractions and 10 Gy in one fraction (as a boost after external beam radiation therapy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kishan et al . showed good local recurrence rates and low long-term morbidity with HDR [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using ablative radiation dose approach showed that CT-guided interstitial brachytherapy for recurrent anorectal cancer achieved durable tumor control, effective palliation, improved long-term survival, and minimal long-term morbidity [30]. Another study showed that high-dose brachytherapy achieved high local control rates and low toxicity in patients with pelvis tumors that were not readily accessible to other therapies [31]. Taken together, these previous studies and the present study suggest that brachytherapy could achieve high-precision treatment of tumors of the pelvic area, with minimal damage to other organs and tissues.…”
Section: Discussionmentioning
confidence: 99%